Peran Strategic Foresight dalam Mempertahankan Sustaibable Capability Organisasi Menuju Inovasi Manajemen - Putri Pratiwi; Antonius Juniadhi Soekendar (Universitas Sains dan Teknologi Komputer, 2023)
This study aims to examine the role of strategic foresight and its ability to support the development of management innovation processes within organizations. This study uses a narrative literature review approach involving potential interactions of three main topics, namely: strategic foresight, management innovation, and management cognition. The results of the study explain that each individual has a character from birth to being able to see the future. Then the capability of foresight in this organization must be developed and continuously maintained by both stakeholders in the organization's management and employees. Before implementing a foiresight strategy, it is necessary to understand in depth managerial cognition as the basis for its application. Furthermore, the development of a well-managed strategic foresight will become a management innovation so as to be able to maintain organizational sustainability. This conceptual paper lays a foundation that can be used as further research in determining strategic foresight capabilities in relation to managerial dynamic capabilities. The results of this paper can be used by organizations that have a long history of facing challenges in capturing the challenges of changing business environments in the future.